RESPON PEGAWAI IAIN PAREPARE TERHADAP PRODUK PEMBIAYAAN BANK SYARIAH - Fadhliyah Ulfah Rustan; Sitti Jamilah Amin; Syahriyah Semaun (Institut Agama Islam Negeri Parepare, 2019)
Response is interpreted as a response, reaction and answer. A response will appear from receiving the message after a series of communications. Financing is one of the bank's main tasks, namely the provision of funds provision facilities to meet the needs of the parties which constitute a unit deficit. Employee response is used in this case to find out how much employees respond well or are interested in financing Islamic banks. This research is descriptive qualitative using a phenomenology approach. Therefore, the authors chose to use qualitative research methods to determine how to search, collect, manage, analyze data from research results and draw conclusions.The results of the study show that: 1) The financing system on Islamic bank products uses four different patterns or systems, namely: profit sharing system, buying and selling system, rental system, loan system. 2) Facilities provided by Islamic banks in the form of providing funds to meet the needs of parties with a profit sharing system. 3) Respondents' responses indicate that most respondents gave positive responses. This condition gives the impression that the employee's response to Islamic banking is perceived positively by respondents. Of the various types of products in Islamic banks, only the savings that are most sought after by sharia bank customers and their reasons for choosing these products because of sharia-compliant, lawful and safe Islamic bank products.